Normalising deviance in construction project organizations: a case study on the collapse of Carillion. Issue 12 (1st December 2020) - Hajikazemi, Sara; Aaltonen, Kirsi; Ahola, Tuomas; Aarseth, Wenche; Andersen, Bjorn
Abstract: In 2018, the Construction giant Carillion went into compulsory liquidation costing the UK taxpayers an estimated £148m. According to our analysis performed on the case, the demise of Carillion was the result of accumulation of failures and normalisation of deviations from good practice. The purpose of this study is to better understand how deviance can become the norm such that actors in the context of the construction organisations such as Carillion, come to adopt deviant practices rather than respecting their accepted industry codes and ethos. This study is based on an in-depth analysis of publicly available data on the case of Carillion. Our aim is to better understand the process of normalisation of deviance and its potential effect on organisations. Our analysis of the case revealed three specific types of normalised deviance: late payments to suppliers, aggressive accounting and payment of high dividends to shareholders despite the troubled financial status of the firm. The results of our work contribute to theory by showing that normalisation of deviance is a gradual process which can be influenced by actors both within the focal organisation as well as actors in its environment. The managerial implications highlight the need for all actors in the construction sector to become more aware of the normalising deviance process and its potential negative effects, which can be mitigated by stronger adherence to controls in the external environment in which the organisation operates.